PENINGKATAN HASIL BELAJAR LAY UP KIRI BOLA BASKET MELAUI METODE LATIHAN BAGIAN (STUDI PADA SISWA KELAS XI IPA I SMAN 2 NGANJUK TAHUN AJARAN 2012-2013) - ARI CHRISTIANTO, BAYU (Jurnal Pendidikan Olahraga dan Kesehatan, 2013)
Abstract When we teach physical education subject there are many problems that we should face. In basketball terms, students often get difficulties when they have to deal with left lay up test. It was predicted that students ability is still low. Considering that the succeed of physical education subject is depend on the students ability to absorb the lesson, it is important to solve the problems and barrier. Many problems and barrier that the students have to face and this research try to find out is it section training method can increase the students ability in basketball left lay up. This research include in action research or PTK. The research divided into 3 terms that will be done in 3 meetings. Each term has four steps which are planning, action, observation and reflection. The result of the research shows that section training method can increase the percentage of students which can done left lay upwhen they are trained individually. In first terms the percentage is 67,33%. It increase to 70,66% in second term. Beside from the percentage, the amoun of students that can fullfill left lay up exam automatically increase. There are 19 students in first term able to do left lay up. In second term there 22 students. The conclution of this research is the increasing of left lay upstudentsablity in basketball learning in class XI IPA 1 Senior High School2 Nganjuk the result is good enough. Keywords: The increasing basketball left lay up learning, part method